How does science and technology finance affect the agricultural green development: an interpretation from the perspective of rural human capital and agricultural industrial agglomeration - Yao, Sheng; Wu, Guosong; Zhang, Shu (Frontiers in Sustainable Food Systems, 2025)
How to achieve a win-win situation between agricultural economic growth and environmental protection has become an urgent issue to be resolved. This study takes China as an example and employs econometric methods to explore the impact of science and technology finance on agricultural green development and its underlying mechanisms. The findings indicate that science and technology finance has a significant positive impact on agricultural green development and can effectively promote it. This conclusion remains robust after replacing the explained variables, adding control variables, removing samples from municipalities, and conducting endogeneity tests. The impact of science and technology finance on agricultural green development is significant across different regions, showing no obvious regional differences. Rural human capital acts as a mediator in the relationship between science and technology finance and agricultural green development, while agricultural industrial agglomeration has a certain “masking effect” on this relationship. The impact of science and technology finance on agricultural green development exhibits a complex non-linear relationship. When science and technology finance is used as a threshold variable, it shows a significant positive marginal effect that increases; however, when rural human capital and agricultural industrial agglomeration are used as threshold variables, it shows a significant positive marginal effect that decreases. Future research can be further expanded in three areas: first, using spatial econometric models to study the spatial spillover effects of science and technology finance on agricultural green development; second, identifying more mediating variables and incorporating them into the research framework to more comprehensively demonstrate the mechanisms through which science and technology finance affects agricultural green development; third, data at the municipal level are used for the relevant analysis to address the issue of insufficient detail in studies that rely on provincial-level data.